Bilingualism and English Dictation Performance of Iranian Primary Level Students - Aynaz Azari (International Journal of Practical and Pedagogical Issues in English Education)
The concept of linguistics transcends specific languages or communities in today's rapidly evolving world. Bilingualism has become increasingly prevalent in various countries, even in smaller cities. In many nations, the formal language of education differs from students' native tongues, and this distinction can exert both positive and negative influences on students' academic performance. Concurrently, the English language is experiencing a surge in popularity in Iran, with many individuals eager to acquire proficiency in this global language. This comparative survey aims to explore the impact of bilingualism on the dictation scores of second-grade elementary students studying English at the Iran Language Institute (ILI). The study involves 30 bilingual students in Tabriz and 30 monolingual students in Tehran, encompassing both genders. To ensure the comparability of students' educational levels, a preliminary step involved administering the Raven intelligence test. The resulting scores were subjected to ANOVA analysis. Subsequently, a dictation test, consisting of 40 words, was administered to the students, and their scores were subjected to an independent t-test. This dictation test underwent rigorous design and validation processes, which included input from four elementary school teachers. The final findings of the study indicate that there is no statistically significant relationship between bilingualism and dictation scores, nor is there a significant correlation between gender and dictation scores.